2000
DOI: 10.1080/03079450050118467
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ is expressed in both gut and spleen duringEimeria tenellainfection

Abstract: The effect of primary infection and subsequent challenge with Eimeria tenella on interferon-g (IFN-g ) production in the spleen and caeca of Light Sussex chickens was assessed. The ability of splenocytes to proliferate and produce IFN-g in response to mitogen stimulation ex vivo was determined. Differences in the kinetics of IFN-g production suggested that the spleens of infected birds contain a subpopulation of T cells, primed to produce IFN-g , which migrate from the spleen in response to a secondary infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Cytokines synthesized and secreted by leukocytes play important regulatory roles during the immune response to infection. In avian coccidiosis, it was clear that IFN-γ was produced by the host at sites of infection (Rothwell et al 2000;Yun et al 2000), and IFN-γ release has been used to screen for protective antigens against E. tenella infections (Breed et al 1999). In this report, IFN-γ levels in the serum samples were significantly higher when compared with those of the PBS group (p<0.05).…”
Section: Discussionmentioning
confidence: 42%
“…Cytokines synthesized and secreted by leukocytes play important regulatory roles during the immune response to infection. In avian coccidiosis, it was clear that IFN-γ was produced by the host at sites of infection (Rothwell et al 2000;Yun et al 2000), and IFN-γ release has been used to screen for protective antigens against E. tenella infections (Breed et al 1999). In this report, IFN-γ levels in the serum samples were significantly higher when compared with those of the PBS group (p<0.05).…”
Section: Discussionmentioning
confidence: 42%
“…Lee et al (2011Lee et al ( , 2012 indicated that antibodies and thus Th2 response also play a role in C. perfringens defense. Regarding Eimeria, IFN-c up-regulation was also seen before in the intestine (Laurent et al, 2001) and the spleen (Rothwell et al, 2000) of first-time E. tenella infected chickens. Rothwell et al (2000) did not observe this effect in previously immunised chickens which complies with the findings of the present study.…”
Section: Discussionmentioning
confidence: 81%
“…In avian coccidiosis, it is clear that IFN-␥ is produced by the host at sites of infection (78,112), and IFN-␥ release has been used as a measure of the T-cell response to coccidial antigens (68,73). Treatment of coccidia-infected chickens with recombinant chicken IFN-␥ (89) improved weight gains with respect to uninfected controls (55,64).…”
Section: Immunobiologymentioning
confidence: 99%